2020
DOI: 10.1002/adma.202003818
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Detectivity Limits of Organic Near‐Infrared Photodetectors

Abstract: Near-infrared (NIR) light detection is key to an ever-growing demand for technical solutions in applications such as surveillance systems, facial recognition, industrial sorting and inspection, pulse oximetry, optical coherence tomography, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
184
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 127 publications
(194 citation statements)
references
References 51 publications
(75 reference statements)
10
184
0
Order By: Relevance
“…This problem can be circumvented by using narrow-gap polymer donors such as PBTQ(OD) or PTTBAI, which show strongly redshifted EQE spectra when blended with PC70BM as previously reported. 27 As shown in Figure 2c, U app is around 22 meV in this case. While deviations of the type U app > + 10 meV are due to the presence of other absorbing species like CT states or deep trap states, small deviations of U app around are likely caused by interference effects, i.e.…”
Section: Figure 1 | Eqe Andsupporting
confidence: 53%
“…This problem can be circumvented by using narrow-gap polymer donors such as PBTQ(OD) or PTTBAI, which show strongly redshifted EQE spectra when blended with PC70BM as previously reported. 27 As shown in Figure 2c, U app is around 22 meV in this case. While deviations of the type U app > + 10 meV are due to the presence of other absorbing species like CT states or deep trap states, small deviations of U app around are likely caused by interference effects, i.e.…”
Section: Figure 1 | Eqe Andsupporting
confidence: 53%
“…2c , where 30 meV. The problem can be circumvented by using narrow-gap polymer donors such as PBTQ(OD) or PTTBAI, which show strongly redshifted EQE spectra when blended with PC 70 BM as previously reported 35 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Examples for EQE tails partially dominated by b , the neat donor absorption or by c , the neat acceptor absorption hence showing in some parts of the spectrum. EQE spectra of PTTBAI:PC 70 BM and PBTQ(OD):PC 70 BM are taken from reference 35 . …”
Section: Resultsmentioning
confidence: 99%
“…─ 0.1 V, is barely influenced by shunt , hence D (─ 0.1 V) ≈ 0 . 13 It was further suggested that for narrow-gap blends, D (─ 0.1 V) decreases exponentially with increasing CT . CT from the blend as the intercept of the measured EQEPV and calculated EQEEL.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as the bandgap energy decreases, 0 is known to increase relative to shunt . In narrow-gap organic semiconductor blends designed for near-infrared photodetection, it was observed recently that D in reverse bias shows almost ideal diode behaviour, 13 allowing for D to be fitted with eq. 1.…”
Section: Introductionmentioning
confidence: 99%